Authority control ontologies in the field of linked open data - Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2013)
Based on the approach of the role that documentary languages develop in the linked open data environment, two ontologies for publishing authority control files are briefly analysed: Mads/RDF and the GND ontology. We consider the need to contemplate the linked open data reality in a more inclusive and global perspective, in which not only datasets are interconnected, but also controlled vocabularies and description models.